Making art history in Europe after 1945 - Haro García, Noemi de; Mayayo, Patricia; Carrillo Castillo, Jesús Ma. 1966- (Routledge, Taylor & Francis Group, 2022)
This book analyses the intermeshing of state power and art history in Europe since 1945 and up to the present from a critical, de-centered perspective. Devoting special attention to European peripheries and to under-researched transnational cultural political initiatives related to the arts implemented after the end of the Second World War, the contributors explore the ways in which this relationship crystallised in specific moments, places, discourses and practices. They make the historic hegemonic centres of the discipline converse with Europe’s Southern and Eastern peripheries, from Portugal to Estonia to Greece. By stressing the margins’ point of view this volume rethinks the ideological grounds on which art history and the European Union have been constructed as well as the role played by art and culture in the very concept of ‘Europe.’
Acknowledgements: "Several of the contributors to this volume met in Madrid in June 2015 for the conference "Politics, State Power and the Making of Art History in Europe after 1945"."
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Geschichte 1945-2000; Demokratie; Ost-West-Konflikt; Totalitarismus; Kulturpolitik; Kunstgeschichte -- Fach; Staatsgewalt; Kunstgeschichtsschreibung; Europa; Konferenzschrift -- Politics, State Power and the Making of Art History in Europe after 1945 -- 06.2015 -- Madrid; Aufsatzsammlung